Efeito da introdução de resíduo de cinza de forno cerâmico em massa para cerâmica estrutural - Lucena, Maurílio de Medeiros (2008)
The red ceramics and structural ceramics, as they are known, include ceramic materials made by blocks of seals and structures, bricks, tiles, smail flagstones manacles, rustic floors and ornamental materials. Their fabrication uses raw material such as clay and clay sites, with some content of impurity. It has good durability and mechanical strength to compression, low cost, making it one of the mainly used materials in civil engineering. The incorporation of many industrial activities residue to ceramic products is a technological alternative for reducing the environmental impact caused by its carefree disposal. This incorporation can promote chemical change and inertness of metals from residue, by fixation in the glassy phase of ceramic during the burning stage. The main aim of this project is to study the technical feasibility of the addition of ceramic oven ash into formulations of mass for structural ceramics. In this project two kinds of clay (plastic and non-plastic) were used, as well as the ash from firewood used in the process of burning of structural ceramics. A group of experiments was outlined, which permitted the evaluation of the influence of the burning cycle in different temperatures of the ash content in formulations for ceramic blocks through technological properties, mechanical behavior and microstructure. Five samples were processed of each one of the masses of plastic and non-plastic clay without addition of ash and with addition of ash on the percentages of 10 % and 20 %, for temperatures of 850 °C, 950 °C, 1050 °C and 1150 °C, obtained through sinterization process. Among the studied compositions, the one which presented best performance was the mass of clay with 10 % of ash, at temperature of 1150 °C, with the smallest absorption of water, the smallest apparent porosity, specific apparent mass a bit over the others and greatest mechanical resistance to flexion. The composition made confirmed the technical feasibility of the use of ash in the mass for structural ceramics with maintenance of its necessary characteristics for its purposes